TRAINING OF SOCIAL MEDIA MARKETING (TIKTOK SHOP AND FACEBOOK) IN STARS BAKERY, KENDAL REGENCY FOR BUSINESS PROMOTION - Liesta Verawati; Muhamad Syaeful Anwar (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Social media marketing via Tiktok Shop and Facebook has become an important strategy in today's business world because these platforms have a large reach and diverse active users. Stars Bakery has not utilized this optimally because its business promotion techniques still use word-of-mouth. The problems faced will have serious long-term impacts, such as product problems that are not widely known by customers, which will lead to a decrease in sales. This activity is carried out in the form of material presentation and training. Training conducted regarding creating Facebook and Tiktok Shop business accounts. Participants in this training are owners and employees at Stars Bakery. This activity was carried out at Stars Bakery because of the promotional techniques carried out. This community service activity aims to assist partners in selling and promoting their products widely with the aim of making their products known to the wider community, increasing brand awareness and increasing sales at Stars Bakery Kendal. The solution offered by this community service activity is social media marketing training through Tiktok Shop and Facebook. The results of this community service activity show that partners, namely Stars Bakery, are satisfied with the training provided. After attending this training, partners plan to use Tiktok Shop and Facebook as media for product promotion and sales.